THE PROBLEM OF WOMEN’S EDUCATION IN THE UKRAINIAN AND BRITISH FEMINIST DISCOURSE (ON THE BASIS OF THE NOVELS BY ELIZABETH GASKELL AND OLHA KOBYLIANSKA) - Turchanska, O. S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article deals with the problem of women’s self-consciousness and education in the feminist discourse of the Ukrainian and English literature. The research is carried out on the basis of typological comparison of the novel by Elizabeth Gaskell «Wives and Daughters» and the novel by Olha Kobylyanska «Valtz melancolique». Education, consciousness and social status of the Ukrainian and British women at the end of the XIXth – beginning of the XXth century are analyzed. Similar and different points in solving the problem of women’s education in the literary works of the Ukrainian and British writers are identified.